Nonwoven fabric coated with core-shell and hollow nanofiber membranes for efficient sound absorption in buildings. (1st April 2022) - Hajimohammadi, Mahnaz; Soltani, Parham; Semnani, Dariush; Taban, Ebrahim; Fashandi, Hossein
Abstract: Current fibrous sound absorbers used in buildings cannot fully satisfy the requirements of sound absorption at low-frequency bands. These demands may be met by engineered multi-layered structures, which are not always practical solutions because of either bulky or heavy structures. It has been well-established that the incorporation of nanofibrous structures with conventional fibrous sound absorbers takes the advantage of enhancing their sound absorption performance, without increasing their weight and thickness. In this study, core-shell and hollow nanofibrous membranes were electrospun on the front or back side of a nonwoven fabric using coaxial electrospinning for 4, 6, and 8 h. Morphological analysis of samples was performed using FE-SEM and TEM techniques. The FE-SEM and TEM images of the nanofibrous membranes confirmed the production of bead-free and core-shell nanofibers. The acoustic behavior of specimens was investigated by the impedance tube technique. The findings showed that when the nanofibrous structure is electrospun on the back side of the nonwoven fabric, the absorption mechanism belongs to the viscosity resistance type. In this case, the acoustic performance is enhanced with the increase of nanofibrous structure thickness. It was found that hollow nanofibers provide superior acoustic behavior as compared with core-shell structures. It was also found that when the nanofibrous membrane is electrospun on the front side of the nonwoven fabric, the mechanism of sound absorption changes to resonance type. The results pointed to the promising sound absorption properties of specimens at low and middle-frequency bands. The findings showed that with the increase of membrane thickness, acoustic performance is improved at both low and middle-frequency bands, and the absorption peak shifts toward the lower frequencies. For the structures composed of core-shell nanofibers electrospun for 4, 6, and 8 h, the absorption peak occurred at frequencies of 1250, 1000, and 800 Hz, respectively. The peaks for the structures made of hollow nanofibers appeared at 800, 630, and 500 Hz, respectively. Highlights: Lightweight sound absorbers with long service life were produced Efficient sound-absorbing construction material at low-frequency bands was produced Hollow nanofibers provide superior acoustic performance as compared with solid ones Designed fibrous structures show promising acoustic behavior at low frequencies Incorporation of nanofibrous structure in nonwoven leads to high sound absorption